2009
DOI: 10.1152/ajpgi.00064.2009
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of motor and sensory pathways of the peristaltic reflex by cannabinoids

Abstract: This effect has generally been attributed to their ability to prejunctionally inhibit release of acetylcholine from excitatory motor neurons that mediate, in part, the ascending contraction phase of the peristaltic reflex. In the present study we examined the effect of cannabinoids on the other transmitters known to participate in the peristaltic reflex using a three-compartment preparation of rat colon that allows separation of ascending contraction, descending relaxation, and the sensory components of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…In vivo, inhibition of FAAH and MAGL in mouse intestine was shown to lead to increased levels of anandamide and 2-AG, respectively, also resulting in reduced motility Duncan et al 2008a;Alhouayek et al 2011). Anandamide seems to play an important role in the regulation of peristaltic reflex pathways within the ENS of rodents (Grider et al 2009). In contrast to CB 1 , the CB 2 receptor may not be involved in the physiological control of gut motility, except in the inflamed gut (Duncan et al 2008b).…”
Section: Gastrointestinal Motilitymentioning
confidence: 99%
“…In vivo, inhibition of FAAH and MAGL in mouse intestine was shown to lead to increased levels of anandamide and 2-AG, respectively, also resulting in reduced motility Duncan et al 2008a;Alhouayek et al 2011). Anandamide seems to play an important role in the regulation of peristaltic reflex pathways within the ENS of rodents (Grider et al 2009). In contrast to CB 1 , the CB 2 receptor may not be involved in the physiological control of gut motility, except in the inflamed gut (Duncan et al 2008b).…”
Section: Gastrointestinal Motilitymentioning
confidence: 99%
“…In fact, all the components of the peristaltic reflex are affected, at least in the rat colon, in which CBs inhibited the ascending contraction and concomitant substance P release, the descending relaxation and concomitant vaso-active intestinal peptide release, and the sensory limb and concomitant calcitonin gene-related peptide release via CB1 receptor activation [25]. …”
Section: Cannabinoids Reduce Gastrointestinal Motor Functionmentioning
confidence: 99%
“…77 Pharmacological studies have demonstrated that anandamide and various CB 1 agonists inhibit gastrointestinal motility in rodens in vivo and in isolated ileum and colon from both animals and humans. 20,80,81 In clinical trials with rimonabant for nicotine cessation or obesity, it was seen that incidence of diarrhea was higher in patients receiving rimonabant than with placebo.…”
Section: Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%